Pengaruh Penerapan Sistem Pengendalian Manajemen Terhadap Kinerja Manajerial(Studi Empiris pada Perusahaan Manufaktur di Kabupaten Sukoharjo) - Nur Romadhani, Putri; , Eny Kusumawati, SE., MM., AK, CA (2016)
The purpose of this study was to determine the effect of the application of management control structure, influence on the performance audit of financial accountability, the effect of government accounting standards on financial accountability. This research was conducted at the Company's Plastics in Grogol Sukoharjo. This study uses a quantitative approach, because the data used in the form of numbers. The samples in this study using purposive sampling method. Samples in this study as many as 72 managers. Penggujian used in this research is multiple linear regression analysis using SPSS 21. The results showed that the management control structure variables positive effect on managerial performance and process management control positive influence on managerial performance.